AB1461-HPR Frequency of rheumatoid factor isotypes in paraguayan patients with rheumatoid arthritis. (12th June 2018) - Roman, L; Riquelme-Granada, S.; Avila-Pedreti, G.; Acosta-Colman, I.; Acosta, M.E.; de Guillen, I.; Duarte, M.; Filartiga, M.T.; Cabrera-Villalba, S.
Abstract : Background: Rheumatoid Arthritis is a chronic rheumatic disease characterised by polyarticular inflammation. The rheumatoid factor is one of the most known prognostic markers, not only its presence, but also the levels. It also presents different isotypes (IgG, IgM, IgA), which can affect the course of the disease. Objectives: To analyse the presence of different rheumatoid factor (RF) isotypes in Paraguayan patients with rheumatoid arthritis (RA) and to study their association with clinical and analytical characteristics. Methods: Descriptive, cross-sectional study. A large number of clinical and serological variables were recorded. The anti-CCP 3.1 and Rheumatoid factor (RF) isotypes IgA, IgG, and IgM were measured in serum samples by ELISA (enzyme-linked immunosorbent assay) (NV<17 U/ml). Statistical analysis was performed using SPSS v.23. Quantitative variables were characterised by their means and standard deviations, while the qualitative variables were characterised according to the percentage of patients. The comparison of clinical and serological variables was performed using the chi-squared test and the student test respectively for qualitative and quantitative variables. Results: 103 patients with RA were included, 86.4% were female, with a median age of onset of 44.7±13.6 years, and the mean disease duration was 7.13±7.03 years. The olygoarticular onset was the most frequent (46.6%). 13.7% were smokers. Extra-articular manifestations were present in 13.5%. The most frequent treatment was methotrexate (84.3%). Erosions were observed in 43.2% of patients. 28% were in remission of the disease measured by the DAS28 index. The average of HAQ was 0.47%±0.58. 91.3% had anti-CCP positive, the mean anti-CCP levels were 290.5±152.8 U/mL. RF isotypes was observed in 75.7%, 53.4% and 38.8% for IgM, IgA and IgG respectively. Mean levels were as follow, IgA 85.62±56.6 U/mL, IgM 96.7±30.9 U/mL, IgG 70.98±72.42 U/mL. 32% of the patients had 2 isotypes of RF, while 25.2% had the 3 isotypes. The 57.3% had ≥2 isotypes of RF. We did not find significant differences when comparing gender, age, disease duration, form of onset, extra-articular manifestations, smoking status, erosions, disease activity, HAQ, treatment, between the different RF isotypes, and levels, except in the presence of anti-CCP with the RF-IgM isotype (p<0.000). Conclusions: This is the first study of RF isotypes in Paraguayan patients with RA. The most frequent isotype of RF was IgM. More than 50% of patients had 2 or more RF isotypes. The majority of patients with positive RF had high levels of different isotypes, being the highest IgM. Disclosure of Interest: None declared